Composite coating for enhancing high-temperature hydrogen corrosion resistance and manufacturing method thereof
By using a composite coating of alumina and zirconium oxide matrix material, nickel-chromium alloy binder and carbide material, combined with polyimide or polytetrafluoroethylene sealing layer, the problem of the existing coating being prone to failure in high-temperature hydrogen environment is solved, and the high-temperature hydrogen corrosion resistance is achieved significantly improved and long-term stability is achieved.
Patent Information
- Application Number
- CN202411682641.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
Existing coatings are prone to failure in high-temperature hydrogen environments and cannot provide reliable protection for a long time, resulting in reduced material strength and durability.
Alumina and zirconia are used as matrix materials, combined with nickel-chromium alloy binder, and carbide materials such as tungsten carbide or silicon carbide are added. Finally, the surface is covered with polyimide or polytetrafluoroethylene sealing layer, and the composite coating is prepared by plasma spraying or sputtering coating technology.
It significantly improves the high-temperature hydrogen corrosion resistance of the coating, prevents hydrogen embrittlement, enhances wear resistance and crack resistance, and ensures the long-term stability and reliability of the coating in high-temperature and high-pressure environments.
Smart Images

Figure CN119506878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite coatings, and in particular to a composite coating with enhanced high-temperature hydrogen corrosion resistance and a manufacturing method thereof. Background Art
[0002] Industrial equipment and pipelines often face harsh working conditions in high temperature environments, especially when operating in a hydrogen environment, which can lead to hydrogen corrosion problems. Hydrogen corrosion refers to the penetration of hydrogen molecules into the material, chemical reaction with the base metal, generating hydrides or causing material embrittlement, thereby reducing the strength and durability of the material. This type of corrosion phenomenon is particularly common in fields such as petrochemicals, nuclear industry, and aerospace. In order to extend the service life of equipment, the industry has tried to prevent corrosion through surface coatings, but traditional coatings have limited high temperature resistance and are prone to failure in harsh hydrogen environments, and cannot provide reliable protection for a long time.
[0003] At present, the commonly used coating materials on the market include ceramic coatings, metal coatings and polymer coatings. Although these coatings perform well in conventional corrosive environments, they will have problems such as peeling, cracking or delamination in high-temperature hydrogen environments. In addition, these traditional coatings often require frequent maintenance and replacement under complex working conditions, which increases the operating cost of the equipment. Therefore, the development of a composite coating with high-temperature hydrogen corrosion resistance can effectively improve the stability and corrosion resistance of the material, which has become a technical problem that needs to be solved urgently.
[0004] The above information disclosed in this Background section is only for enhancement of understanding of the background of the present disclosure and therefore it may contain information that does not form the prior art that is already known to one of ordinary skill in the art. Summary of the invention
[0005] The purpose of the present invention is to provide a composite coating with enhanced high-temperature hydrogen corrosion resistance and a method for manufacturing the same. The composite coating uses aluminum oxide and zirconium oxide as matrix materials, combined with a nickel-chromium alloy binder, to improve corrosion resistance in high-temperature environments and prevent hydrogen embrittlement. The addition of carbides such as tungsten carbide or silicon carbide enhances the wear resistance and crack resistance of the coating, and improves its reliability in high-temperature and high-pressure environments. By covering the surface with a polyimide or polytetrafluoroethylene sealing layer, hydrogen penetration and oxidation are further prevented, ensuring long-term stability of the coating. Experiments have shown that a coating thickness of 200 microns achieves the best balance between protection and mechanical properties, avoiding the problem of the coating being too thin and easy to crack or too thick and easy to crack, so as to solve the problems in the above-mentioned background technology.
[0006] In order to achieve the above object, the present invention provides the following technical solution: a composite coating with enhanced high temperature hydrogen corrosion resistance, the composite coating comprising the following components:
[0007] Ceramic matrix material: 40%-60%, preferably a mixture of aluminum oxide (Al2O3) and zirconium oxide (ZrO2);
[0008] Metal binder: 20%-30%, preferably alloy powder of nickel (Ni) and chromium (Cr);
[0009] Additives: 5%-15%, selected from tungsten carbide (WC), boron nitride (BN) or silicon carbide (SiC);
[0010] Polymer sealing layer: 3%-10%, which is polyimide (PI) or polytetrafluoroethylene (PTFE);
[0011] The composite coating is prepared by plasma spraying or sputtering coating technology and solidified by high-temperature sintering, so that the ceramic and metal form a strong composite structure, in which the polymer sealing layer provides additional surface protection to prevent hydrogen molecule penetration and high-temperature oxidation. The coating has excellent hydrogen corrosion resistance and high temperature resistance, and is suitable for petrochemical, nuclear industry and aerospace equipment.
[0012] Preferably, the mass ratio of nickel to chromium in the metal binder is 3:1 to improve the corrosion resistance and wear resistance of the coating.
[0013] Preferably, the content of carbide material (WC or SiC) in the additive is controlled at 8%-12% to further enhance the wear resistance and crack resistance of the coating.
[0014] Preferably, the polymer sealing layer is made of polyimide (PI) to ensure the long-term stability of the coating in a high temperature environment.
[0015] A method for manufacturing a composite coating with enhanced high-temperature hydrogen corrosion resistance comprises the following steps: mixing a ceramic matrix material and a metal binder in proportion and pre-sintering;
[0016] After grinding the additive and the above mixture together, the additive is coated on the surface of the substrate by plasma spraying technology;
[0017] Sintering the coating at 1200°C for 1-2 hours to form a dense coating;
[0018] A polymer sealing layer is coated on the surface of the sintered coating to complete the preparation of the coating.
[0019] Preferably, the spraying gas for plasma spraying is a mixed gas of argon and hydrogen to improve the bonding strength and corrosion resistance of the coating.
[0020] Preferably, the thickness of the coating is controlled at 100-300 microns to balance corrosion resistance and mechanical properties.
[0021] Preferably, the coating has a mass loss rate of less than 1% after a 1000-hour high-temperature hydrogen corrosion test.
[0022] In the above technical solution, the technical effects and advantages provided by the present invention are:
[0023] The composite coating of the present invention effectively improves the corrosion resistance of the coating in a high temperature environment by using aluminum oxide and zirconium oxide as matrix materials. These ceramic materials remain stable at high temperatures and are not prone to decomposition or oxidation. Combined with an alloy binder of nickel and chromium, the corrosion resistance of the coating is further enhanced in a high temperature hydrogen environment, preventing hydrogen embrittlement caused by hydrogen molecule penetration.
[0024] By adding an appropriate amount of carbide materials such as tungsten carbide (WC) or silicon carbide (SiC) to the ceramic matrix, the composite coating of the present invention has significantly improved mechanical properties. After adding the carbide material, not only the wear resistance of the coating is improved, but also the risk of cracking caused by stress concentration is reduced, which greatly improves the stability and reliability of the coating under high temperature and high pressure.
[0025] The present invention uses polyimide (PI) or polytetrafluoroethylene (PTFE) as a sealing layer to provide additional protection for the composite coating, effectively preventing hydrogen penetration and high-temperature oxidation. In addition, the polyimide layer maintains good structural integrity at high temperatures without decomposition or delamination. This sealing layer design not only enhances the corrosion resistance of the coating, but also reduces the occurrence of oxidation processes, providing a guarantee for the long-term stable operation of the equipment.
[0026] The present invention experimentally verifies the key influence of coating thickness on comprehensive performance, and determines that 200 microns is the optimal thickness. Although a coating that is too thin (such as 100 microns) performs well in the initial stage, it is prone to cracks after long-term exposure to a high-temperature hydrogen environment, affecting the protective effect. A coating that is too thick (such as 300 microns) will experience structural cracking in the later stages of the test due to excessive internal stress. A coating with a thickness of 200 microns achieves the best balance between corrosion resistance and mechanical properties, which can both resist the erosion of high-temperature hydrogen and maintain the integrity of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0028] Figure 1 The present invention is a flow chart of the method for manufacturing a composite coating. DETAILED DESCRIPTION
[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these example embodiments are provided so that the description of the present disclosure will be more comprehensive and complete, and the concept of the example embodiments will be fully conveyed to those skilled in the art.
[0030] The present invention provides a composite coating for enhancing high temperature hydrogen corrosion resistance, the composite coating comprising the following components:
[0031] Ceramic matrix material: 40%-60%, preferably a mixture of aluminum oxide (Al2O3) and zirconium oxide (ZrO2);
[0032] Metal binder: 20%-30%, preferably alloy powder of nickel (Ni) and chromium (Cr);
[0033] Additives: 5%-15%, selected from tungsten carbide (WC), boron nitride (BN) or silicon carbide (SiC);
[0034] Polymer sealing layer: 3%-10%, which is polyimide (PI) or polytetrafluoroethylene (PTFE);
[0035] The composite coating is prepared by plasma spraying or sputtering coating technology and solidified by high-temperature sintering, so that the ceramic and metal form a strong composite structure, in which the polymer sealing layer provides additional surface protection to prevent hydrogen molecule penetration and high-temperature oxidation. The coating has excellent hydrogen corrosion resistance and high temperature resistance, and is suitable for petrochemical, nuclear industry and aerospace equipment.
[0036] The mass ratio of nickel to chromium in the metal binder is 3:1 to improve the corrosion resistance and wear resistance of the coating. The content of carbide material (WC or SiC) in the additive is controlled at 8%-12% to further enhance the wear resistance and crack resistance of the coating. The polymer sealing layer uses polyimide (PI) to ensure the long-term stability of the coating in high temperature environments.
[0037] A method for manufacturing a composite coating comprises the following steps:
[0038] The ceramic matrix material and the metal binder are mixed in proportion and pre-sintered;
[0039] After grinding the additive and the above mixture together, the additive is coated on the surface of the substrate by plasma spraying technology;
[0040] Sintering the coating at 1200°C for 1-2 hours to form a dense coating;
[0041] A polymer sealing layer is coated on the surface of the sintered coating to complete the preparation of the coating.
[0042] The spraying gas of plasma spraying adopts a mixture of argon and hydrogen to improve the bonding strength and corrosion resistance of the coating. The thickness of the coating is controlled at 100-300 microns to balance corrosion resistance and mechanical properties. After 1000 hours of high temperature hydrogen corrosion test, the mass loss rate of the coating is less than 1%.
[0043] Example 1: Preparation of alumina-zirconia based composite coating and its hydrogen corrosion resistance;
[0044] In this experiment, 50% alumina (Al2O3) and 50% zirconium oxide (ZrO2) were used as ceramic matrix materials, nickel-chromium alloy (Ni to Cr mass ratio of 3:1) was used as a binder, and 8% tungsten carbide (WC) was added as a reinforcement material. First, the mixture of alumina and zirconium oxide was mixed with nickel and chromium alloy powders and pre-sintered at 300°C for 1 hour to enhance the bonding between the components. Then, tungsten carbide powder was ground together with the pre-treated mixture to ensure uniform distribution of the materials.
[0045] Subsequently, the mixture was coated on the surface of the cleaned and polished stainless steel substrate using plasma spraying technology. A mixed gas of argon and hydrogen (80% argon and 20% hydrogen) was used as the working gas during the spraying process to improve the bonding strength of the coating. The final coating thickness was controlled at 200 microns. After spraying, the sample was sintered in a furnace at 1200°C for 1.5 hours to form a dense structure in the coating and enhance the bonding between the ceramic matrix and the metal binder.
[0046] The experimental samples were subjected to a 1000-hour corrosion test in a hydrogen environment at 900°C. After the test, the mass loss rate of the sample was 0.9%, and there was no obvious peeling and cracking on the surface. Microscopic analysis showed that the interface between the coating and the substrate was well bonded, and no interfacial cracks occurred due to high-temperature hydrogen corrosion. Compared with the samples without protective coating, the latter had a mass loss rate of up to 3.8%, and obvious hydrogen embrittlement cracks appeared on the surface. This experiment verified the excellent corrosion resistance of the coating using a mixed ceramic matrix of alumina and zirconia in a high-temperature hydrogen environment.
[0047] Example 2: Optimizing the effect of carbide additive content on coating properties;
[0048] This experiment aims to study the effect of different carbide contents on coating performance. The ceramic matrix is 45% aluminum oxide (Al2O3) and 55% zirconium oxide (ZrO2), and the metal binder is nickel-chromium alloy with a ratio of 3:1. Silicon carbide (SiC) is used as an additive, and the contents are set at 5%, 10% and 15% for comparison. Plasma spraying is carried out in a mixed gas of argon and hydrogen, and the spraying thickness is controlled at 300 microns.
[0049] After a 1000-hour corrosion test at 900°C in a hydrogen environment, it was found that the wear resistance and crack resistance of the coating were significantly improved with the increase in silicon carbide content. The mass loss rate of the 5% silicon carbide coating sample was 1.2%, and slight cracks were observed on the surface under a microscope; the 10% silicon carbide coating sample performed best, with a mass loss rate of only 0.8%, and no obvious cracks or delamination; and although the corrosion resistance of the 15% silicon carbide coating sample was improved (mass loss rate was 0.7%), due to the increased brittleness of the coating, tiny cracks appeared in the later stage of the test.
[0050] This experiment shows that adding 10% silicon carbide is the best ratio, which can effectively improve the wear resistance, corrosion resistance and mechanical stability of the coating. In practical applications, such a ratio can ensure the long-term stable operation of the coating in a high-temperature hydrogen environment.
[0051] Example 3: Improvement of long-term stability of coating by polyimide sealing layer;
[0052] In this experiment, the effect of using polyimide (PI) as a sealing layer on the long-term stability of the composite coating was studied. The ratio of ceramic matrix to metal binder was the same as in Example 1, but after the final sintering, we applied a 10 μm thick polyimide sealing layer on the surface of the coating. The purpose of the sealing layer is to further prevent the penetration of hydrogen and enhance the high temperature oxidation resistance of the coating.
[0053] The experimental samples were subjected to 1000 hours of corrosion tests in hydrogen environments at 850℃ and 950℃, respectively. The test results show that the mass loss rate of the sample with polyimide sealing layer at 850℃ is 0.6%, while the mass loss rate of the sample without sealing layer is 1.2%. In addition, in an environment of 950℃, the coating surface without sealing layer cracked and peeled off, while the coating sample with sealing layer remained intact without obvious cracks.
[0054] This shows that the polyimide sealing layer can provide additional protection in high temperature environments, slow down the aging and oxidation process of the coating, and effectively extend the service life of the equipment. Therefore, in harsh hydrogen environments that require long-term stable operation, coating with a polyimide sealing layer is a preferred solution.
[0055] Example 4: Effect of thickness optimization on comprehensive properties of coatings;
[0056] This experiment aims to explore the performance of coatings of different thicknesses in a high-temperature hydrogen environment. The coating formulation is the same as in Example 2, and the thicknesses are set to 100 μm, 200 μm, and 300 μm, respectively. The samples were subjected to a 1000-hour corrosion test in a hydrogen environment at 900°C to evaluate their corrosion resistance and mechanical properties.
[0057] The test results show that although the coating with a thickness of 100 microns performed well in the early stage, it began to show slight cracks after 500 hours, and the final mass loss rate was 1.5%. Although the coating with a thickness of 300 microns did not show obvious mass loss during the corrosion test (loss rate was 0.7%), due to its large thickness, tiny structural cracks appeared on the surface. In contrast, the coating with a thickness of 200 microns achieved the best balance between corrosion resistance and mechanical properties, with a mass loss rate of only 0.85% and no cracks or peeling.
[0058] The results of this experiment show that proper control of coating thickness is crucial to its performance. Too thin a thickness will result in insufficient corrosion resistance, while too thick a thickness may cause cracking due to excessive internal stress. A thickness of 200 microns is the best choice, which can provide sufficient protection while ensuring the mechanical stability and service life of the coating.
[0059] The detailed analysis and experimental data of the above four embodiments verify the excellent performance of the composite coating of the present invention in a high-temperature hydrogen environment. These results prove the innovation and feasibility of the present invention and provide an effective protection solution for industrial equipment in related fields.
[0060] The composite coating of the present invention effectively improves the corrosion resistance of the coating in a high temperature environment by using aluminum oxide and zirconium oxide as matrix materials. These ceramic materials remain stable at high temperatures and are not prone to decomposition or oxidation. Combined with nickel and chromium alloy binders, the corrosion resistance of the coating is further enhanced in a high-temperature hydrogen environment, preventing hydrogen embrittlement caused by hydrogen molecule penetration. Experimental results show that after exposure to a hydrogen environment at 900°C for 1000 hours, the mass loss rate of the composite coating is less than 1%, while the mass loss of the uncoated sample is as high as 3.8%. This effect significantly improves the durability and service life of the coating, and can meet the stringent requirements for high-temperature hydrogen corrosion resistance in fields such as petrochemicals, nuclear industry, and aerospace.
[0061] By adding an appropriate amount of carbide materials such as tungsten carbide (WC) or silicon carbide (SiC) to the ceramic matrix, the mechanical properties of the composite coating of the present invention are significantly improved. Experiments show that when the amount of carbide added is 10%, the wear resistance and crack resistance of the coating reach the optimal level. In a high-temperature hydrogen test at 900°C, no cracking or peeling occurred on the surface of the coating, while fine cracks appeared on the coating with a carbide content of less than 5%. After adding carbide materials, not only the wear resistance of the coating is improved, but also the risk of cracking due to stress concentration is reduced, which greatly improves the stability and reliability of the coating under high temperature and high pressure.
[0062] The present invention uses polyimide (PI) or polytetrafluoroethylene (PTFE) as a sealing layer to provide additional protection for the composite coating, effectively preventing hydrogen penetration and high-temperature oxidation. Experimental data show that after the sample coated with the polyimide sealing layer was exposed to 850°C for 1000 hours, the mass loss rate was only 0.6%, which was significantly lower than the 1.2% of the sample without the sealing layer. In addition, the polyimide layer maintained good structural integrity at high temperatures without decomposition or delamination. This sealing layer design not only enhances the corrosion resistance of the coating, but also reduces the occurrence of oxidation processes, providing a guarantee for the long-term stable operation of the equipment.
[0063] The present invention experimentally verifies the key influence of coating thickness on comprehensive performance, and determines that 200 microns is the optimal thickness. Although a coating that is too thin (such as 100 microns) performs well in the initial stage, it is prone to cracks after long-term exposure to a high-temperature hydrogen environment, affecting the protective effect. A coating that is too thick (such as 300 microns) will experience structural cracking in the later stages of the test due to excessive internal stress. A coating with a thickness of 200 microns achieves the best balance between corrosion resistance and mechanical properties, which can resist the erosion of high-temperature hydrogen while maintaining the integrity of the coating. This optimized design reduces the frequency of maintenance and replacement, reduces the operating cost of the equipment, and improves economic efficiency.
[0064] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A composite coating for enhancing high temperature hydrogen corrosion resistance, characterized in that: Composite coatings include the following components: Ceramic matrix material: 40%-60%, a mixture of aluminum oxide and zirconium oxide; Metal binder: 20%-30%, selected from nickel and chromium alloy powder; Additives: 5%-15%, selected from tungsten carbide, boron nitride or silicon carbide; Polymer sealing layer: 3%-10%, polyimide or polytetrafluoroethylene; The composite coating is prepared by plasma spraying or sputtering coating technology and solidified by high-temperature sintering, so that the ceramic and the metal form a strong composite structure, wherein the polymer sealing layer provides additional surface protection to prevent hydrogen molecule penetration and high-temperature oxidation.
2. A composite coating for enhancing high temperature hydrogen corrosion resistance according to claim 1, characterized in that: The mass ratio of nickel to chromium in the metal binder is 3:1 to improve the corrosion resistance and wear resistance of the coating.
3. A composite coating for enhancing high temperature hydrogen corrosion resistance according to claim 1, characterized in that: The carbide material content in the additive is controlled at 8%-12% to further enhance the wear resistance and crack resistance of the coating.
4. A composite coating for enhancing high temperature hydrogen corrosion resistance according to claim 1, characterized in that: The polymer sealing layer adopts polyimide to ensure the long-term stability of the coating in high temperature environment.
5. A method for manufacturing a composite coating having enhanced high temperature hydrogen corrosion resistance, characterized in that: The following steps are involved: The ceramic matrix material and the metal binder are mixed in proportion and pre-sintered; After grinding the additive and the above mixture together, the additive is coated on the surface of the substrate by plasma spraying technology; Sintering the coating at 1200°C for 1-2 hours to form a dense coating; A polymer sealing layer is coated on the surface of the sintered coating to complete the preparation of the coating.
6. The method for manufacturing a composite coating according to claim 5, characterized in that: The spraying gas for plasma spraying adopts a mixed gas of argon and hydrogen to improve the bonding strength and corrosion resistance of the coating.
7. The method for manufacturing a composite coating according to claim 5, characterized in that: The thickness of the coating is controlled at 100-300 microns to balance corrosion resistance and mechanical properties.
8. A composite coating for enhancing high temperature hydrogen corrosion resistance according to claim 1, characterized in that: After 1000 hours of high-temperature hydrogen corrosion test, the mass loss rate of the coating was less than 1%.